Degradation of Trypan Blue in wastewater by sunlight-assisted modified photo-Fenton reaction - Dutta, A. (Taylor and Francis Inc., 2015)
Homogeneous Fenton reaction (Fe2+/H2O2) is one of the most important advanced oxidation processes to generate (Formula presented.) free radicals for degradation of organic pollutants in wastewater. Degradation of an azo dye (Trypan Blue) by solar photo-Fenton process has been investigated in this work using a batch reactor under sunlight. Instead of acidic pH used in conventional Fenton reaction, neutral pH is used here to modify the same. Effects of the changes in process parameters, including dosage of ferrous sulphate and hydrogen peroxide as well as pH have been examined. Percent degradation was observed to increase with increasing H2O2 dosing up to a particular critical value. Increase in FeSO4 dose and acidic medium increased degradation. Complete decolourization was achieved after 2Â h when 500Â mL of 5.2 Ã 10â4Â molÂ Lâ1 dye aqueous solution at pH 7 was oxidized with 2.8 Ã 10â4Â molÂ Lâ1 of ferrous sulphate and 0.03Â molÂ Lâ1 of H2O2 under sunlight of average intensity 281Â WÂ mâ2. Mineralization of dye pollutant was monitored by COD measurement. Additionally, FTIR analysis also supported degradation. A kinetic model was developed and validated with experimental data. Â© 2014 Balaban Desalination Publications. All rights reserved.